Documents on the papal plenary indulgences 1300-1517 preached in the Regnum Teutonicum - Jenks, Stuart (Later medieval Europe, 2018)
Front Matter -- Copyright Page -- Dedication -- Acknowledgements -- Introduction -- A Brief Guide for the Uninitiated -- Jubilee Indulgence 1300 -- Jubilee Indulgence 1350 -- Jubilee Indulgence 1389 -- Crusade Indulgence against the Hussites 1420 -- Plenary Indulgence of the Council of Basel for Financing the Negotiations with the Greeks on the Union of Both Churches 1436/38 -- Jubilee Indulgence 1450 -- Crusade against the Turks 1455 -- Crusade against the Turks 1463 -- Crusade Indulgence against King George Podiebrad of Bohemia 1465/71 -- Jubilee Indulgence 1475 -- Indulgence for the Church of Saintes 1476/88 -- Plenary Indulgence for the Order of St Mary Magdalene in Strasbourg 1479 -- Indulgence for the Order of St John of Jerusalem in Defense of Rhodes 1479/82 -- Indulgence in Aid of the War against the Turks 1489 -- Jubilee Indulgence 1500 -- Indulgence in Aid of the War against the Turks 1501/03 -- Indulgence in Aid of the War against the Russians and Tartars in Livonia 1503/06 -- St Peter Indulgence 1506 -- Indulgence in Aid of the War against the Russians and Tartars in Livonia 1507/10 -- Indulgence in Aid of the Reconstruction of the Towers of the Constance Minster 1513/14 -- Indulgence for the Hospital of the Holy Spirit in Rome 1514/18 -- Indulgence in Aid of the Dominicans of Augsburg 1514/17 -- Indulgence for the Cathedral of Trier 1515/16 -- Indulgence for the Repair of the Dikes in the Burgundian Netherlands 1515/18 -- Indulgence in Aid of the Reconstruction of the Parish Church of Brüx/Most 1516/18 -- St Peter Indulgence 1514/18 -- St Peter Indulgence 1516/18 -- Conclusion -- Chronological List of Documents -- Back Matter -- References.